Does physical fitness and parenting transformational style predict happiness and wellbeing and distress in adolescents? (¿La condición física y el estilo parental transformacional predicen la felicidad, el bienestar y angustia psicológica de los adolesce - Ruiz-Ariza, Alberto; De la Torre-Cruz, Manuel J.; Appelqvist-Schmidlechner, Kaija; Tamminen, Nina; Martínez-López, Emilio J. (Retos, 2020)
Abstract: There is a growing interest on the relationships between family functioning and behaviors that promote physical and psychological well-being in children and adolescents. The aim of the study was to assess the association of parenting transformational style with happiness, wellbeing and distress in adolescents, beyond of physical fitness influence, and independently of age and body mass index. Data were gathered among 868 Spanish schoolchildren aged 12-16 years (M=14.07, SD=1.24) with a self-administered questionnaire and conducting physical fitness tests. The findings showed that age and the perception of a maternal and paternal transformational style predicted happiness, wellbeing and distress in adolescent girls. In boys, only the parental transformational style acted as a significant predictor, independently of fitness level. Muscular strength contributed to explain the wellbeing in adolescent girls independently of transformational style; however, it did not happen in speed-agility and cardiorespiratory capacity. Findings suggest that promotion of parenting transformational style is beneficial to the psychological wellbeing, above all in younger adolescents. In girls, promotion of higher muscular strength could contribute to improve happiness and wellbeing independently of parental transformational styles. Resumen: Hay un creciente interés en el examen de la relación entre funcionamiento familiar y conductas que promueven el bienestar físico y psicológico de niños y adolescentes. El objetivo de este estudio fue evaluar la asociación entre el estilo parental transformacional y la felicidad, bienestar y angustia psicológica, más allá de la posible influencia de la condición física, edad e índice de masa corporal de un grupo de adolescentes. Se obtuvieron valores de 868 jóvenes españoles con edades comprendidas entre los 12-16 años de edad (M=14.07, SD = 1.24) en medidas de autoinforme y pruebas de condición física. Los resultados mostraron que la edad y la percepción de un estilo materno y paterno transformacional predijeron la felicidad, bienestar y angustia psicológica en las chicas adolescentes. En los chicos, solo el estilo transformacional parental actuó como un predictor significativo, más allá de la condición física. La fuerza muscular contribuyó a explicar el bienestar de las chicas adolescentes de forma independiente al estilo transformacional, algo que no ocurrió con la velocidad y la capacidad cardiorrespiratoria. Los resultados sugieren que la promoción de un estilo parental transformacional es beneficiosa para el bienestar psicológico, especialmente, en los jóvenes adolescentes. En las chicas, la promoción de una mayor fuerza muscular podría contribuir a la mejora de la felicidad y el bienestar, de un modo independiente, al estilo parental transformacional.